2019
DOI: 10.3389/fmicb.2019.01350
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Microbiome Related to Rusty Roots of Panax ginseng and Evaluation of Antagonists Against Pathogenic Ilyonectria

Abstract: Plant roots host diverse microbes that are closely associated with root fitness. Currently, the relationship between microbes and rusty roots of Panax ginseng remains unclear. Here, we described the root-associated microbiome in rusty and healthy ginseng by metagenomic sequencing of 16S rRNA and ITS regions. Being enriched in Diseased-roots (Dr) of ginseng and their rhizosphere soil, the fungus of Ilyonectria , was identified as the most probable cause of the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 58 publications
5
33
0
Order By: Relevance
“…Most soil-borne diseases are caused by fungi under the CC systems. For instance, pathogenic fungi caused soil-borne diseases in the continuous peanut [13] and soybean cropping [127] systems by reducing the abundance of anti-pathogenic taxa [119,175]. In another study, the soil fungal diversity was significantly reduced after three years of continuous notoginseng cropping.…”
Section: Soil-borne Fungal Diseasesmentioning
confidence: 97%
“…Most soil-borne diseases are caused by fungi under the CC systems. For instance, pathogenic fungi caused soil-borne diseases in the continuous peanut [13] and soybean cropping [127] systems by reducing the abundance of anti-pathogenic taxa [119,175]. In another study, the soil fungal diversity was significantly reduced after three years of continuous notoginseng cropping.…”
Section: Soil-borne Fungal Diseasesmentioning
confidence: 97%
“…Before transplanting, ten soil samples were collected from random locations in each plot and combined to generate one bulk soils (BL). Then, rhizosphere soil samples were collected at one of the three developmental stages of P. notoginseng in each year: (1) vegetative (V, May); (2) owering (F, Jul), (3) root growth (R, Oct), namely 2-year V (2YV), 2-year F (2YF), 2-year R (2YR), 3-year V (3YV), 3-year F (3YF), and 3-year R (3YR). At each sampling time, ten randomly selected healthy plants were removed from each plot, and mixed to generate one rhizosphere sample [26].…”
Section: Developmental Stages Sampling Experimentsmentioning
confidence: 99%
“…e relationship between rhizospheric microorganisms and rusty root symptoms in P. ginseng has been extensively investigated. Several studies have demonstrated that rusty root can be caused by bacteria, fungi, or a combination of both [25,26]. For example, Farh et al reported that the rusty root of P. ginseng was caused by Cylindrocarpon destructans var.…”
Section: Introductionmentioning
confidence: 99%
“…destructans [11], while Lu et al investigating the pathogenicity of Ilyonectria robusta against the root of P. ginseng using repeated inoculation, highlighted that I. robusta could be the causative agent of rusty root of P. ginseng in China [27]. Recent studies have also indicated that the Ilyonectria fungus was the most likely cause of rusty root in P. ginseng, as this pathogen was found to be enriched in the rhizosphere soils of plants exhibiting rusty root symptoms [11,25]. Furthermore, Guan et al isolated Fusarium redolens from diseased roots of P. ginseng and reported this pathogenic fungus as a new causative agent of P. ginseng root rot in China [28].…”
Section: Introductionmentioning
confidence: 99%